2014
DOI: 10.1037/scp0000014
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of relations between psychotherapist religiousness/spirituality and therapy-related variables.

Abstract: Although psychotherapy is a value-laden undertaking, the ways in which therapists' values affect their work are not well understood. Religion and spirituality (R/S) are potentially powerful influences on therapy that need to be studied in greater depth. To summarize existing research and encourage additional work, the authors conducted a systematic review of studies examining the relations between psychotherapists' R/S and therapy attitudes and behaviors, the therapeutic relationship, and treatment outcomes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 42 publications
0
42
0
2
Order By: Relevance
“…Therapists can work with family members to identify the belief about their faith that are in conflict and identify ways in which those beliefs can co-exist again. The integration of faith constructs into therapy-even when not shared by the therapist-is significantly linked to good outcomes (Cummings et al, 2014).…”
Section: Interventions For Crisis Of Faithmentioning
confidence: 99%
“…Therapists can work with family members to identify the belief about their faith that are in conflict and identify ways in which those beliefs can co-exist again. The integration of faith constructs into therapy-even when not shared by the therapist-is significantly linked to good outcomes (Cummings et al, 2014).…”
Section: Interventions For Crisis Of Faithmentioning
confidence: 99%
“…For example, to assess discriminant validity for the Spiritually Derived Intervention Checklist, Canda and Furman (2010) compared Christians' and Atheists/Agnostics' responses. Similarly, as outlined in Cummings et al (2014) review, having an RS affiliation has been positively related to RS intervention use (Shafranske and Maloney 1990), more self-disclosure of RS beliefs (Payman 2000), and therapists' view of appropriateness of discussing RS (Beatty et al 2007). …”
Section: Other Elements Of Rs and The Integration Of Clients' Rsmentioning
confidence: 99%
“…Similarly, in social work, Sheridan (2009) literature review found four out of five studies had personal RS (measured as either religious affiliation, participation in communal RS services, or personal RS practices) as a significant predictor of higher RS intervention use. More recently, Cummings et al (2014) conducted a systematic review regarding the relationship between practitioners' RS and therapy attitudes and behaviors, and found seven of eight identified articles indicated a positive, significant relationship between the two. Further, five out of six studies found a positive association between therapists' RS and self-rated competence with integrating clients' RS, and eight out of 10 studies found therapists' RS predicted the use of RS interventions in treatment.…”
Section: Other Elements Of Rs and The Integration Of Clients' Rsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, one of the largest predictors of practitioners' views and behaviors related to integrating clients' RS is their own intrinsic religiosity, regardless of their faith tradition (Oxhandler et al 2015;Cummings et al 2014). Further, spiritual or religious counselors tend to integrate more RS therapeutic behaviors with clients, affirm and communicate respect for clients' RS beliefs, solicit client feedback concerning the therapy they are receiving, and advocate for the self-determination and autonomy of religious clients (Frazier and Hansen 2009).…”
Section: Religion/spirituality In Health and Mental Health Treatmentmentioning
confidence: 99%